Avaliação clínica da laserterapia na prevenção da mucosite oral e sua relação com níveis salivares de interleucina-8, óxido nítrico e mieloperoxidase em pacientes submetidos ao transplante de células tronco hematopoiéticas - Salvador, Daniella Ribeiro Naves (2017)
Oral mucositis (OM) is the most common debilitat- ing complication among patients undergoing hematopoietic stem cell transplantation (HSCT). Photobiomodulation thera- py (PBM) has shown beneficial effects in the treatment of OM, but few studies have evaluated its biological effects. This study evaluated the effect of PBM on the reduction of OM severity in patients undergoing HSCT and its relation to the modulation of the inflammatory response. Fifty-one pa- tients were randomly assigned to two groups: PBM [submitted to PBM from admission (AD) to D+7] (n = 27) and control (n = 24) [received oral hygiene]. OM severity was assessed daily using the WHO scale. Saliva samples were collected on AD, D+7, and hospital discharge (HD) to measure CXCL8/ interleukin 8, using cytometric bead array analysis and nitrite (NO) and myeloperoxidase (MPO) using colorimetric methods. PBM significantly reduced the severity of OM from D+7 to D+11 (p < 0.05). All non-interventional patients (controls) who developed grade 2 or higher OM induced an increase of CXCL8 in saliva (n = 14) on D+7. PBM led to a decrease in CXCL8 on D+7 in 85% of patients, while 70.8% of patients in the control group presented an increase in this chemokine (p = 0.007). NO decreased from AD to D+7 in the PBM group (p > 0.05). MPO significantly decreased on D+7 in both groups (p < 0.05). PBM brought about a reduction in the severity of OM in patients undergoing HSCT, and this reduction was associated with a decrease in CXCL8 salivary levels.